Determinants of Tax Consultant Career Interest Among Accounting Graduates - Putu Edi Sutrisna; Anita Kusuma Dewi; Damayanti Damayanti (Academia Open, 2026)
General Background The growing number of registered taxpayers increases demand for tax professionals, while the number of tax consultants remains comparatively limited. Specific Background Accounting graduates possess competencies relevant to taxation but consider multiple internal and external factors when choosing a professional pathway. Knowledge Gap Previous findings regarding work environment, self-motivation, self-efficacy, and tax knowledge are inconsistent and are frequently based on students or professions other than tax consulting. Aims Grounded in the Theory of Planned Behavior, this quantitative survey examines work environment, self-motivation, self-efficacy, and tax knowledge in relation to interest in pursuing a tax consultant career among 168 accounting graduates. Data were analyzed using multiple linear regression in SPSS 26. Results Work environment, self-motivation, and tax knowledge showed positive and significant statistical relationships with career interest, whereas self-efficacy was not statistically significant. Simultaneously, the four variables were significant and accounted for 63% of the variation in career interest. The findings indicate stronger roles for subjective norm and attitude toward behavior than for perceived behavioral control. Novelty The study applies the Theory of Planned Behavior to accounting graduates rather than limiting analysis to students and jointly examines internal and external career-choice factors in the tax consulting context. Implications Career development initiatives can prioritize supportive work conditions, intrinsic motivation, and tax knowledge, while future research should examine additional variables and alternative analytical approaches. Highlights: Work environment, intrinsic motivation, plus fiscal knowledge showed positive significant coefficients. The four-factor model jointly explained 63% of variance within the dependent outcome. Subjective norm plus attitude toward behavior were more prominent than perceived behavioral control. Keywords: Career Interest, Self-Efficacy, Self-Motivation, Tax Knowledge, Work Environment